Atropisomeric amides as chiral ligands: using (-)-sparteine-directed enantioselective silylation to control the conformation of a stereogenic axis - Clayden, J; Johnson, P; Pink, J; Helliwell, M (2000)
An enantiomerically pure (1-trimethylsilyl)ethyl group, constructed by a (-)-sparteine-directed enantioselective quench of a laterally lithiated tertiary aromatic amide, exerts powerful thermodynamic control over the conformation of the adjacent tertiary amide substituent. Ortholithiation and functionalization of the amide in the 6-position allows the single amide conformer to be trapped as an enantiomerically and diastereoisomerically pure amide atropisomer. Protodesilylation of the amide gives functionalized atropisomeric amides with a stereogenic axis of single absolute configuration, whose barriers to racemization have been determined by polarimetry. Enantiomerically pure amides bearing phosphine substituents are effective ligands in a Pd-catalyzed allylic substitution reaction-the first use of a nonbiaryl atropisomer as a chiral ligand-and give products with 90% ee. The rate of racemization of the phosphine-substituted amide is powerfully influenced by the presence of palladium.